Визначення напрямку реконструкції заземлювального пристрою - Руденко, С.С.; Коліушко, Д.Г; Кащеєв, О.В. (Електротехніка і електромеханіка, 2017)
На основі розрахункових експериментів проаналізовано можливі випадки невідповідності заземлювальних пристроїв нормативним вимогам та способи їх реконструкції за вимогами до напруги дотику та опору. Визначено ефективність вказаних напрямків реконструкції як з точки зору електробезпеки, так і матеріально-трудових витрат. На основании расчетного эксперимента проанализированы возможные случаи несоответствия заземляющих устройств нормативным требованиям и способы их реконструкции по требованиям к напряжению прикосновения и
сопротивлению. Определена эффективность указанных направлений реконструкции как с точки зрения электробезопасности, так и материально-трудовых затрат. Purpose. In paper the most efficient and economical way for
bringing the grounding system of power facilities into compliance with requirements of normative parameters was determined. Methodology. The determination was based on the comparison of the calculated values of touch voltage and length of
additional electrodes for reconstruction of grounding system by
two ways. To calculate the software based on the method of
point current source which located in the three-layer soil,
method guidance potential, Gauss method and the method of
ordinary least squares was used. Results. For three possible
cases amount of material and labor costs for the reconstruction
and modernization of the grounding system while maintaining
the equipotent grounding system and allowable touch voltage
was defined. Originality. For the first time the effectiveness the
reconstruction of grounding system for requirements of touch
voltage, not to her of resistance, both in terms of electrical safety and in terms of material and labor costs proved. Practical
value. The implementation of results saves a national scale
funds for modernization and reconstruction of existing grounding systems of power facilities.